A questão da identidade na lírica de Mário de Sá-Carneiro - Beuttenmuller, Eric (2007)
The theme of identity is very important and discussed when we talk about Modernity. In the Portuguese modernism, for example, besides Mário de Sá-Carneiro, we have the emblematic figure of Fernando Pessoa and his heteronyms that assure a lot of discussions about the theme. The objective of this research is to analyze the question of identity in Mario de Sá-Carneiro s lyrics. Throughout his poems, the main focus is the relation made up among the image that the persona has about itself and another one, ideal, that it creates for itself, plus the consequences that the established conflict generates. In all the poems written by the renowned Portuguese poet, there is a strong perceptible difference between these images. From Mário de Sá-Carneiro s poems, we will ascertain the way the persona tries to create an own identity. We will also notice how, in a historic period that demands fragmentation, the persona searches for its identity, according to a conception of subject that is perfect and self-centered. We will realize how and why this attempt is condemned to fail.